Mothers of small-bodied children and fathers of vigorous sons live longer - Valge, Markus; Meitern, Richard; Hõrak, Peeter (Frontiers in Public Health, 2023)
Life-history traits (traits directly related to survival and reproduction) co-evolve and materialise through physiology and behaviour. Accordingly, lifespan can be hypothesised as a potentially informative marker of life-history speed that subsumes the impact of diverse morphometric and behavioural traits. We examined associations between parental longevity and various anthropometric traits in a sample of 4000-11 000 Estonian children in the middle of the 20th century. The offspring phenotype was used as a proxy measure of parental genotype, so that covariation between offspring traits and parental longevity (defined as belonging to the 90th percentile of lifespan) could be used to characterise the aggregation between longevity and anthropometric traits. We predicted that larger linear dimensions of offspring associate with increased parental longevity and that testosterone-dependent traits associate with reduced paternal longevity. 12 of 16 offspring traits were associated with mothers' longevity, while three traits (rate of sexual maturation of daughters and grip strength and lung capacity of sons) robustly predicted fathers' longevity. Contrary to predictions, mothers of children with small bodily dimensions lived longer, and paternal longevity was not linearly associated with their children's body size (or testosterone-related traits). Our study thus failed to find evidence that high somatic investment into brain and body growth clusters with a long lifespan across generations, and/or that such associations can be detected on the basis of inter-generational phenotypic correlations.